Socio-cultural change influences the changes of Simalungun religion. Issue 2 (3rd April 2022) - Saragih, Hisarma; Ridwan, Muhammad; Adisaputera, Abdurahman
ABSTRACT: This study analyzes the historical phenomena of zending in Batak tribe community. It focuses on the transition of Christianity among the Simalungun people, by using the primary and secondary sources tracked from various library locations, church archives, national archives in Jakarta, and private collections. The theme is categorized into cultural history, with source search ( heuristic ), source criticism, formulation of facts ( aufassung ), and presentation of new thoughts ( darstellung ), all narrated as historical stories. Other secondary sources came from a number of books, articles, and magazines, published in various eras. The cause of mass conversion among the Simalungun people is apparently related to the feudal structure of their society. The zendelings used both the community structure approach and customary approach. Consequently, the development of RMG zending activities in the Simalungun community, besides causing religious conversion from the Sipajuh Begu-begu tribe religion to Christianity, also gave rise to structural changes in the community.